2007
DOI: 10.1111/j.1365-2133.2007.07817.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dermatology Life Quality Index: assessing the efficacy of biological therapies for psoriasis

Abstract: The DLQI banding concept provides a further tool to assess the impact of biologics on HRQoL of patients with psoriasis. Based on retrospective application of DLQI bands to published RCT data, infliximab, followed by etanercept, showed the greatest improvement in the overall HRQoL paralleled by a 75% improvement in the Psoriasis Area and Severity Index. However, some publications did not provide absolute baseline DLQI values, making interpretation of data and comparison between the agents difficult. Side-to-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 27 publications
(42 reference statements)
1
72
0
3
Order By: Relevance
“…Several papers have dealt with the relationship between the improvement in PASI score and that in DLQI using data from the studies on biological therapy. Katugampola et al 5 reported that a superior improvement in the overall QOL was paralleled by a PASI 75 response based on reports of randomized placebo-controlled trials with infliximab, etanercept, efalizumab and alefacept. Further, the EXPRESS study of infliximab showed that the percent improvement in DLQI score was 90% or more in PASI 75 and PASI 90 responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have dealt with the relationship between the improvement in PASI score and that in DLQI using data from the studies on biological therapy. Katugampola et al 5 reported that a superior improvement in the overall QOL was paralleled by a PASI 75 response based on reports of randomized placebo-controlled trials with infliximab, etanercept, efalizumab and alefacept. Further, the EXPRESS study of infliximab showed that the percent improvement in DLQI score was 90% or more in PASI 75 and PASI 90 responders.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers report that a marked improvement in PASI indicates a remarkable improvement in DLQI. 5,6 However, there is no study reporting on the relationship between the two treatment goals: namely, a PASI 75 response and a DLQI of 0 or 1. Infliximab, an antihuman tumor necrosis factor-a monoclonal antibody, is prescribed for patients with psoriasis throughout the world, in the hope of meeting the treatment goals based on the proven high percentage of patients achieving a PASI 75 (PASI 75 response rate) or a PASI 90 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In verschiedenen randomisierten, kontrollierten klinischen Studien konnte gezeigt werden, dass die Behandlung von Psoriasis mit Infliximab und Etanercept im Vergleich zu Placebo zu einer Verbesserung der LQ führte [24]. Eine anfängliche starke LQ-Beeinträchtigung von Punktewerten ≥ 10 im DLQI konnte mit Etanercept nach 12 bis 24 Wochen auf eine moderate LQ-Beeinträch-tigung (Mittelwerte bei 6 bis 10 Punkten) gesenkt werden.…”
Section: Forschungsbeispiele Aus Der Dermatologieunclassified
“…Auch wenn die LQ-Erfassung in der Patientenversorgung viele Vorteile mit sich bringt, ist diese noch nicht ausreichend in die dermatologische Praxisroutine implementiert [24,30]. Um diese Implementierung zu fördern, bedarf es neben der Wissensvermittlung, welche Relevanz die LQ-Erfassung hat und wie man LQ adäquat erfassen kann, noch weiterer Schritte.…”
Section: Ausblickunclassified
“…The greatest improvements in quality of life are with infliximab followed by etanercept. 6 To date the literature on combination therapy involving biologicals is extremely limited. This area needs to be further explored to improve patient outcomes and important drug safety issues such as skin cancer.…”
Section: Phototherapy and Standard Systemic Drugs In Severe Psoriasismentioning
confidence: 99%